LET’S PLAYING GAME: THE EFFECTS OF BRAND-GAME-SELF CONGRUITIES ON PLAYER'S ATTITUDE TOWARDS BRANDS IN ADVERGAMES - Yuaniko Paramitra; Daniel Tumpal H. Aruan (Universitas Mercu Buana, 2017)
Abstract. The purpose of this research is to examine the extent to which game-selfcongruity, brand-self congruity and brand-game congruity simultaneously affect gameplayer‟s attitude towards the advertised brand in advergame. This research extends theextant literature that asserts that the player‟s attitude towards brand is not onlyinfluenced by perceived congruity between brand and game, but it is also affected bythe player‟s self-concept and how he/she identifies him/herself to the game and thebrand. The results showed that brand-game congruity has significant effect on player‟sattitude towards the brand and perceived entertainment was found to mediate the effectof game-self congruity on player‟s attitude. Findings of this research can helpmarketers to better design and promote marketing approaches to consumers by takinggame-self and brand-self congruities into account.Keywords: Advergame, game-self congruity, brand-game congruity, brand-selfcongruity